The Dual Role of Crowding in Hedonic Retail Environments: How Human and Spatial Crowding Shape Excitement, Eustress, Satisfaction, and Impulsive Buying - Lailatus Sa’diyah; Della Ayu Zonna Lia (Journal of Social Work and Science Education, 2026)
The cosmetic retail industry in Indonesia faces intense competition and increasingly crowded store environments. While prior studies predominantly emphasize the negative consequences of crowding, this study offers a different perspective by examining its potential to elicit positive emotional responses. Drawing on the Stimulus-Organism-Response (SOR) framework, this research investigates the effects of human crowding and spatial crowding on consumers’ excitement and stress, and their subsequent impact on satisfaction and impulsive buying behavior. A quantitative survey of 276 consumers was analyzed using SEM-PLS. The findings reveal that human crowding significantly increases both excitement and stress, while spatial crowding primarily triggers stress without affecting excitement. Notably, both excitement and stress positively influence satisfaction, suggesting that stress in this context may function as eustress (positive stress) rather than purely negative pressure. Furthermore, satisfaction significantly drives impulsive buying behavior. This study offers a novel perspective that retail crowding extends beyond negative implications and introduces the role of eustress in shaping consumer experiences in hedonic retail settings. Practical insights for managing crowding to enhance emotional engagement and stimulate impulsive purchases are discussed.